Enhanced micropropagation protocol for teak (Tectona grandis) through zygotic embryo and in vitro seedling-derived explants - Venkatachalam, Vasudevan; Nakasha, Jaafar Juju; Sinniah, Uma Rani (Springer, 2024)
This study attempted to evaluate the potential use of juvenile explants from seeds and seed-derived seedlings to establish an enhanced micropropagation protocol by optimizing the plant growth regulators that promote induction and multiplication of shoots to produce a large number of teak plantlets. In this study, seed-derived explants, such as cotyledons and zygotic embryos, and seedling-derived explants, such as shoot tips and nodal segments, were first utilized to induce multiple shoots. The maximum number of multiple shoots (9.3 shoots) with a height of 1.5 ± 0.2 cm was produced from zygotic embryos compared with shoot tips (4.3), nodal segments (4.1), and cotyledons (4.0). Approximately 9.3 shoots were obtained from explants cultured on medium supplemented with 2.0 mg L−1 BAP and 0.01 mg L−1 NAA after 5-wk incubation. Upon removal of the elongated shoot (1.5 ± 0.2 cm), the remaining clump of microshoots (< 1.0 cm) was further sub-cultured for three cycles, resulting in 775 shoots in 15 wk. The isolated shoots subjected to elongation under the optimal concentration of 0.1 mg L−1 BAP demonstrated an 80% response, accompanied by the development of shoots with a maximum length of 2.08 cm and a maximum leaf count of 5.4 after 4 wk. The rooting media supplemented with 0.01 mg L−1 NAA facilitated the highest number of roots (3.3) with an average root length of 2.6 cm, resulting in a response of 74% compared with control, which had only a 36% response and 1.8 roots with a root length of 1.6 cm. The rooted plantlets were acclimatized and then successfully transferred to the field. This efficient protocol can result in large-scale propagation of in vitro teak plantlets in the future and offer advantages in terms of healthy and resilient teak plantations.